Implementation of Model View Controller Architecture in Object Oriented Programming Learning - Ester Lumba; Alexander Waworuntu (IJNMT (International Journal of New Media Technology), 2021)
This study aims to provide an overview of the application of software design patterns, namely Model View Controller (MVC) in object-oriented programming learning. In the software development industry, most application development uses frameworks. MVC architecture is a design pattern that is widely used by various frameworks. Students as prospective programmers or software developers must master and be able to translate object-oriented programming concepts into programming languages. In this study, the Java programming language is used to apply the object-oriented concept and implement the MVC architecture. This research resulted in an increase in students' programming skills and abilities as well as being able to apply the MVC architecture in developing applications using Java.